Knowledge Management System Implementation: Expert System / Nor Adilla Mansor - Mansor, Nor Adilla (Universiti Teknologi MARA, Selangor, 2020)
In this millennial era, artificial intelligence is rapidly growth and it is a method that has been used to solve the problem in the variety field such as business, medical, agriculture, mechanical, and so on as a business automation. The usage of this artificial intelligence may allow the computing systems solve the problems roughly at the human level. Even the power of artificial intelligence is quite powerful in this era, but it cannot go beyond the human nature which means it can solve just for a specific problem, but cannot completely replace as a human being. Based on the Yarushkina et.al (2018) the intellectual systems closely related to the artificial intelligence must contain the knowledge of the Problem Area (PrA) and also should have the problem solving methods that can solve the issues in assigning the task such as machine learning methods, knowledge engineering methods, and ontologies method